An estimation of global Aeromonas infection prevalence in children with diarrhoea: a systematic review and meta-analysis - Hamid Sadeghi; Ahad Alizadeh; Majid Vafaie; Mohammad Reza Maleki; Saeideh Gholamzadeh Khoei (BMC, 2023)
Abstract Objectives Diarrhoea is the most commonly related disease caused by Aeromonas. To improve knowledge on prevalence, this systematic review and meta-analysis was performed to evaluate the global prevalence of Aeromonas in children with diarrhoea worldwide. Methods We systematically searched PubMed, Google scholar, Wiley Online Library, ScienceDirect, and Web of sciences to identify all cross-sectional published papers between 2000 and 10 July 2022. After initial scrutinizing, 31 papers reporting the prevalence of Aeromonas in children with diarrhoea were found to be adequate for meta-analysis. The statistical study was accompanied by using random effects models. Results A total of 5660 identified papers, 31 cross-sectional studies encompassing 38,663 participants were included in the meta-analysis. The pooled prevalence of Aeromonas in children with diarrhoea worldwide was 4.2% (95% CI 3.1-5.6%). In the subgroup analysis, the highest prevalence was seen among children in Upper middle-income countries with pooled prevalence of 5.1% (95% CI 2.8-9.2%). The prevalence of Aeromonas in children with diarrhoea was higher in countries with populations of over 100 million people (9.4%; 95% CI 5.6-15.3%), and water and sanitation quality score of less than 25% (8.8%; 95% CI 5.2-14.4%). Additionally, Cumulative Forest Plot showed a decreasing trend in the prevalence of Aeromonas infection in children with diarrhoea over time (P = 0.0001). Conclusion The results of this study showed a better comprehension of Aeromonas prevalence in children with diarrhoea on a global scale. As well as our findings showed that much work is still required to decline the burden of bacterial diarrhoea in countries with high populations, low-level income, and unsanitary water.